Synthetic approaches and biological Activity of chalcones (Eurasian Journal of Research, Development and Innovation, 2024)
Chalcones are the main building blocks for flavonoids and isoflavonoids biosynthesis. Chalcones are made up of a three-carbon, α,β -unsaturated carbonyl system. Chalcones are the products of aromatic aldehyde condensation with acetophenones in the presence of a catalyst. They are useful in the synthesis of pyrazoline, isoxazole, and a variety of heterocyclic compounds because they go through a variety of chemical reactions. For the synthesis of these compounds, a variety of methods and schemes have been reported. Aldol condensation and Claisen-Schmidt condensation are still at the top of the list. Other notable techniques , Chalcones are active lead compounds that can be used to find new medications in medicinal chemistry. This section will explain characteristics and biosynthesis